2002
DOI: 10.1046/j.1096-3642.2002.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

The cladistics and biology of the Callajoppa genus-group (Hymenoptera: Ichneumonidae, Ichneumoninae)

Abstract: A cladistic analysis is presented for the genera of the former ichneumonine tribe Trogini. The tribe Heresiarchini is paraphyletic with respect to the Trogini, and so maintaining Trogini as a separate tribe is unsatisfactory. Within Heresiarchini, the following changes are made: (a) the subtribes Apatetorina and Heresiarchina are referred to as the Apatetor and Heresiarches genus‐groups, (b) the genera of the paraphyletic subtribe Protichneumonina are treated as incerta sedis within Heresiarchini, and (c) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…Recorded hosts of Platylabini mainly belong to Geometridae (Yu et al 2012) and members of the tribe are known as larval-pupal parasitoids (van Veen 1981, Tereshkin 2009). The metasoma morphology is either amblypygous, which is adapted for attacking larvae, or oxypygous, which is adapted for attacking pupae (Heinrich 1960, Hinz 1983, Sime and Wahl 2002. Although Sime and Wahl (2002) suggested that oxypygous species do not strictly attack pupae, none of the species with an amblypygous metasoma were recorded as pupal parasitoids; this indicates that Heinrichiellus is also a larvalpupal parasitoid.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recorded hosts of Platylabini mainly belong to Geometridae (Yu et al 2012) and members of the tribe are known as larval-pupal parasitoids (van Veen 1981, Tereshkin 2009). The metasoma morphology is either amblypygous, which is adapted for attacking larvae, or oxypygous, which is adapted for attacking pupae (Heinrich 1960, Hinz 1983, Sime and Wahl 2002. Although Sime and Wahl (2002) suggested that oxypygous species do not strictly attack pupae, none of the species with an amblypygous metasoma were recorded as pupal parasitoids; this indicates that Heinrichiellus is also a larvalpupal parasitoid.…”
Section: Discussionmentioning
confidence: 98%
“…The metasoma morphology is either amblypygous, which is adapted for attacking larvae, or oxypygous, which is adapted for attacking pupae (Heinrich 1960, Hinz 1983, Sime and Wahl 2002. Although Sime and Wahl (2002) suggested that oxypygous species do not strictly attack pupae, none of the species with an amblypygous metasoma were recorded as pupal parasitoids; this indicates that Heinrichiellus is also a larvalpupal parasitoid. A study on Ichneumon suggested that species with a slender body and long antenna tend to attack hosts pupating above the ground (Tschopp et al 2013); Heinrichiellus also probably attacks hosts pupating above the ground.…”
Section: Discussionmentioning
confidence: 98%
“…Most Trogus were reared from host larvae collected at later larval instars (fourth-fifth); however, several T. lapidator were reared from P. zelicaon caterpillars collected during their first and second larval instars at Saskatoon Hill, Alberta. Trogus pennator (Fabricius 1793), a conspicuous species in eastern North America, is known to oviposit in caterpillars of any age (Sime and Wahl 2002), and T. violaceus Mocsáry 1883 (a synonym of T. lapidator found in Europe: Wahl and Sime 2006), has been shown to parasitize P. hospiton Géné 1839 as early as its second instar (Prota 1962). However, T. lapidator and T. fulvipes have only been documented from caterpillars collected during later (fourth and fifth) larval instars in western Canada (Sperling 1986, Wahl andSime 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Second, although Trogus are specialist parasitoids on swallowtail butterflies, another swallowtail butterfly, Papilio canadensis Rothschild and Jordan 1906, also inhabits these areas (Scott 1986). While Trogus lapidator has not been reared from P. canadensis, there are records of T. fulvipes from this host (Sime and Wahl 2002), which adds another layer of complexity to the population dynamics of these parasitoids. Finally, as noted earlier, the taxonomy of these Trogus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation